Development of a shuttle walking test of disability in patients with chronic airways obstruction. Issue 12 (December 1992) - Singh, S J; Morgan, M D; Scott, S; Walters, D; Hardman, A E
Abstract : BACKGROUND: The aim was to develop a standardised and externally paced field walking test, incorporating an incremental and progressive structure, to assess functional capacity in patients with chronic airways obstruction. METHODS: The usefulness of two different shuttle walking test protocols was examined in two separate groups of patients. The initial 10 level protocol (group A, n = 10) and a subsequent, modified, 12 level protocol (group B, n = 10) differed in the number of increments and in the speeds of walking. Patients performed three shuttle walking tests one week apart. Then the performance of patients (group C, n = 15) in the six minute walking test was compared with that in the second (modified) shuttle walking test protocol. Heart rate was recorded during all the exercise tests with a short range telemetry device. RESULTS: The 12 level modified protocol provided a measure of functional capacity in patients with a wide range of disability and was reproducible after just one practice walk; the mean difference between trial 2 v 3 was -2.0 (95% CI -21.9 to 17.9) m. There was a significant relation between the distance walked in the six minute walking test and the shuttle walking test (rho = 0.68) but the six minute walking test appeared to overestimate the extent of disability in some patients. The shuttle test provoked a graded cardiovascular response not evident in the six minute test. Moreover, the maximal heart rates attained were significantly higher for the shuttle walking test than for the six minute test. CONCLUSIONS: The shuttle walking test constitutes a standardised incremental field walking test that provokes a symptom limited maximal performance. It provides an objective measurement of disability and allows direct comparison of patients' performance.